On the long-cycle variability of the Algol OGLE-LMC-DPV-065 and its stellar, orbital, and disc parameters. Issue 3 (16th May 2019) - Mennickent, R E; Cabezas, M; Djurašević, G; Rivinius, T; Hadrava, P; Poleski, R; Soszyński, I; Celedón, L; Astudillo-Defru, N; Raj, A; Fernández-Trincado, J G; Schmidtobreick, L; et al.
ABSTRACT: OGLE-LMC-DPV-065 is an interacting binary whose double-hump long photometric cycle remains hitherto unexplained. We analyze photometric time series available in archive data sets spanning 124 yr and present the analysis of new high-resolution spectra. A refined orbital period is found of 10${^{\rm d}_{.}}$ 031 6267 ± 0${^{\rm d}_{.}}$ 000 0056 without any evidence of variability. In spite of this constancy, small but significant changes in timings of the secondary eclipse are detected. We show that the long period continuously decreases from 350 to 218 d during 13 yr, then remains almost constant for about 10 yr. Our study of radial velocities indicates a circular orbit for the binary and yields a mass ratio of 0.203 ± 0.001. From the analysis of the orbital light curve, we find that the system contains 13.8 and 2.81 M⊙  stars of radii 8.8 and 12.6 R⊙ and absolute bolometric magnitudes −6.4 and −3.0, respectively. The orbit semimajor axis is 49.9 R⊙ and the stellar temperatures are 25 460 K and 9825 K. We find evidence for an optically and geometrically thick disc around the hotter star. According to our model, the disc has a radius of 25 R⊙, central and outer vertical thickness of 1.6 R⊙ and 3.5 R⊙, and temperature of 9380 K at its outer edge. Two shock regions located at roughly opposite parts of the outer disc rim can explain the light-curve asymmetries. The system is a member of the double periodic variables and its relatively high-mass and long photometric cycle make it similar in some aspects to β Lyrae.